A novel nutritional supplement containing chromium picolinate, phosphatidylserine, docosahexaenoic acid, and boron activates the antioxidant pathway Nrf2/HO-1 and protects the brain against oxidative stress in high-fat-fed rats - Şahin, Nurhan; Akdemir, Fatih; Orhan, Cemal; Aslan, Abdullah; Agca, Can A.; Gencoglu, Hasan; Şahin, Kazım (Taylor & Francis Ltd, 2012)
Aims: A novel nutritional supplement complex (N21 #125) composed of four well-known compounds (chromium picolinate, phosphatidylserine, docosahexaenoic acid, and boron) was designed to improve memory function and maintain brain health. The present study evaluated the complex's potential mechanism of action and its role in reducing oxidative stress in the brain of obese rats fed a high-fat diet (HFD). Methods: Male Wistar rats (n = 40, 8-week-old) were divided into four groups. Group I was fed a standard diet; Group II was fed a standard diet and supplemented with N21 #125; Group III was fed an HFD; and Group IV was fed an HFD and supplemented with N21 #125 for 12 weeks. Results: Rats fed HFD had greater serum C-reactive protein (CRP) and tumor necrosis factor alpha (TNF-alpha) and brain malondialdehyde (MDA) concentrations than rats fed the control diet. Supplementation of N21 #125 decreased CRP, TNF-a, and MDA concentration in rats fed HFD. The levels of brain nuclear factor-E2-related factor-2 (Nrf2), heme oxygenase, extracellular signal-regulated kinases and protein kinase B were lower in rats fed the control diet than for rats fed the HFD. These parameters were increased by supplementation of N21 #125. Discussion: The data indicate that N21 #125 protected the brain from oxidative damage and inflammation induced by the HFD. This effect may be through up-regulation of the transcription factor Nrf2 expression.
Keywords: High-fat diet; Nrf2/HO-1; Oxidative stress